The Stretch-Shortening Cycle Training Increases Agility and Speed in Young Males - Mahmud Yunus; Slamet Raharjo; Irmantara Subagio (Universitas PGRI Palembang, 2023)
The purpose of this study was to demonstrate the effect of stretch-shortening cycle training on developing speed and agility in young males. The method used in this research was pre-experimental with a pre-test-post-test design for one group. Twelve young males aged 20-22 years were recruited as study participants and provided intervention stretch-shortening cycle training at an intensity of 80-90% HRmax, three times per week for six weeks (18 meetings). The Illinois Agility Test (IAT) was used to assess agility, while the 30 Meter Sprint Test was used to assess speed. Speed and agility were measured twice, once before and once after training. A paired-sample t-test was employed for data analysis, with a confidence level of 5%. The findings revealed a considerable improvement in average agility and speed between pre-and post-training (p ≤ 0.01). It was concluded that stretch-shortening cycle training for six weeks proved effective in increasing speed and agility in young males. The results of this study can be used as a basis for recommendations for improving and maintaining physical fitness and the performance of futsal players to achieve optimal performance.